Nocturnes - Faust, Chris (University of Minnesota Press, 2007)
A prominent figure in the Twin Cities art scene, Chris Faust marks the essence of the changing Midwestern landscape by documenting common scenes in an uncommon way. Known for his spectacular panoramic work, Faust is also increasingly admired for his unique night photographs, where he quietly unveils a world we never noticed was there and when the darkest hours evoke a mood of mystery and surrealism. The palette of light and shadow heightens our senses by revealing the stillness and ambiguities of the landscape. Nocturnes, a beautiful collection of more than seventy tritone photographs, is a vi.